Modelling housing supply and monetary policy within the context of global economic turbulence - Liu, Junxiao; London, Kerry (International Journal of Strategic Property Management, 2013)
Housing supply is an essential component of the property sector. Compared with an increasingly strong housing demand, the growth rates of total housing stock in Australia have exhibited a downward trend since the end of the 1990s. Over the same period, the significant adjustments in the Australian monetary policy were being implemented under a turbulent global economic climate. This research aims to identify the relationship between housing supply and monetary policy within the context of global economic turbulence by a vector error correction model with a dummy variable. The empirical evidence indicates that the monetary policy changes and global economic turmoil can significantly affect the supply side of the housing sector in Australia. The models developed in this study assist policy makers in estimating the political impacts in the global context.First Publish Online: 3 Apr 2013